Web et terminologie philologique - Lerat, Pierre (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
A linguistic method for using the Web consists in making requests on strings of characters as long as possible between quotation marks, then confronting the obtained results with other sources. One knows that the Web is “transitory” and is “varying greatly in value”; nonetheless using this method will be efficient. Useful requests are made through classes of objects and sets of predicates (Gross & Guenthner 2002). Comparing frequencies is a good means of evaluating the respective vitality of concurrent terminological phrases and their social uses (official, technical, professional or journalistic texts). So neologisms and archaisms become obvious. If terminology ’s aim is to work on specialized names, professional contents and linguistic knowledge about terms, the Web is a very good tool to validate technical translations, provided philological precautions.